AB0559 ARRHYTHMIAS AND LEFT VENTRICULAR DYSFUNCTION IN PATIENTS WITH SYSTEMIC SCLEROSIS. (2nd June 2020) - López-Núñez, L.; Carrión Barberà, I.; Padró, I.; Molina, L.; Pros, A.
Abstract : Background: Cardiac involvement in systemic sclerosis (SS) is common and one of the leading causes of mortality (up to 31%). Usually, it appears early and in a silent way. It can affect any cardiac structure and present with various manifestations. Cardiac disease worsens the prognosis and increases mortality, so it should be kept in mind in these patients. Objectives: Study the prevalence of arrhythmias in patients with SS, not affected with pulmonary arterial hypertension (PAH) or other cardiac diseases, and establish its association with left ventricular (LV) dysfunction and heart dysautonomia (HD), as well as with other variables that could predict the development of this complication. Methods: Prospective study of a cohort of patients with SS, excluding those with heart disease, PAH or cardiovascular risk factors. All underwent a clinical assessment, blood test with cardiac biomarkers, electrocardiogram (ECG), Holter 24h (HLT) and echocardiogram (TTE), interpreted by an expert cardiologist blind about the patients. Arrhythmias were classified as clinically significant arrhythmias (CSA) or clinically nonsignificant arrhythmias (CNSA) by ECG and HLT. LV diastolic dysfunction (LVDD) was defined as E/e'> 8, LV systolic dysfunction (LVSD) as a global longitudinal strain <20% and HD as a SDNN <100ms. Demographic, clinical and biological data were collected. A follow-up was performed at 6.2 ± 0.9 years. Statistical analysis was performed using SPSS 23 IBM®. Results: 36 patients were included: age 56.7 ± 12.3 years (y), male / female 35/1, disease duration 7 ± 4.1 y. 66% belonged to the limited SS subtype, 66.6% were anti-centromere+, 25% anti-topoisomerase, 2.7% anti-PM/Scl and 2.7% anti-RNA polymerase III+. Raynaud was present in a 100%, telangiectasia in 55.6% and interstitial lung disease in 36.1%. The modified Rodnan skin score (mRSS) was ≤ moderate (0-29 points) in 55.6%; 27.8% had presented digital ulcers that required prostaglandins. 27.8% had LVDD, 22% LVSD, 11.1% LVDD + SD and 16.7% HD. 50% (18/36) of patients had ECG alterations, of which 44% corresponded to CSA (Table 1) and, 55.6% (20/36) HLT alterations, of which 75% were CSA (Table 2 ). 3/36 patients had both HLT and ECG CSA. In 1 patient, impaired LV ejection fraction was detected; in none, valvular disease. 38.8% had elevated NT-proBNP and 13.9% troponin T (TnT). No correlation was found between any parameters and CSA. A correlation was found between mRSS and DLCO (p=0.002), DLCO and digital ulcers (p=0.001), and mRSS and digital ulcers (p=0.005). A correlation was also found between elevated NT-proBNP and TnT (p=0.006) and between elevated NT-proBNP and LVDD (p=0.049). At follow-up after 6.2 ± 0.9 y, 2 patients had died: 1 of neoplasia and 1 of severe biventricular dysfunction 5.2 y after the study. Conclusion: Our data confirm a high prevalence of ventricular arrhythmias and left dysfunction in patients with SS, without heart disease, cardiorespiratory symptoms or HAP, being up to 75% of the arrhythmias CSA. The lack of correlation between CSA and LVSD or DD indicates that arrhythmias could be due, not only to a supposed structural alteration of the myocardium, but to a primary and early cardiac involvement in SS. In addition, the lack of correlation between CSA in ECG and HLT reinforces the importance of a complete cardiac evaluation in these patients to rule out silent cardiac involvement. Disclosure of Interests: LILIAN LÓPEZ-NÚÑEZ: None declared, Irene Carrión Barberà Grant/research support from: I received a grant from the Spanish Rheumatology Foundation (FER) and laboratories KERN PHARMA for a brief stay abroad., Isabel Padró: None declared, Lluis Molina: None declared, Ana Pros: None declared